Transmisi Pengetahuan dan Nilai Budaya Masyarakat Indonesia Ditinjau dari Ajaran Kanuragan Jawa - Jean-Marc de Grave (Antropologi Indonesia, 2000)
This article deals with systems of transmission of knowledge. The author looks into the kanuragan of the Javanese and its transformation into a modern form, along with the consequences of this transformation. Traditional kanuragan instruction is primarily oral and centers on intermediary roles and social intercourse, and it is conducted in space that is cosmographically meaningful. In contrast, modern individualistic instruction-rooted in early Greek philosophy and events in the European Middle Age-is highly formalized and linked to economic concerns, leading to an individualism with little regard for one's surroundings. The author suggests that the Javanese kanuragan has been partially transformed by this modern system. Thus, the transmission of knowledge is increasingly divorced from the transmission of morals and affect that form the basis of one's actions and social relationships. The author also notes that scholars would gain much from understanding the kanuragan in their efforts to understand current Indonesian Society.